2017
DOI: 10.1186/s12936-017-1943-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of fluorescent in situ hybridization and Giemsa microscopy with quantitative real-time PCR technique in detecting malaria parasites in a holoendemic region of Kenya

Abstract: BackgroundEarly and accurate diagnosis of malaria is important in treatment as well as in the clinical evaluation of drugs and vaccines. Evaluation of Giemsa-stained smears remains the gold standard for malaria diagnosis, although diagnostic errors and potential bias estimates of protective efficacy have been reported in practice. Plasmodium genus fluorescent in situ hybridization (P-Genus FISH) is a microscopy-based method that uses fluorescent labelled oligonucleotide probes targeted to pathogen specific rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In this respect, it can be noted that the values provided by the experts from Uganda were in line with some population-based survey studies that calculated the sensitivity of the microscopy using the PCR as gold standard (e.g., [ 5 ]). On the other hand, the values provided by the experts from Kenya and the Democratic Republic of the Congo seemed to be higher than those reported in population-based survey studies where PCR was used as gold standard (e.g., [ 28 , 29 ]). Nonetheless, the one-way sensitivity analyses showed that the true prevalence estimates in all three countries were robust against misspecification of this prior.…”
Section: Discussionmentioning
confidence: 60%
“…In this respect, it can be noted that the values provided by the experts from Uganda were in line with some population-based survey studies that calculated the sensitivity of the microscopy using the PCR as gold standard (e.g., [ 5 ]). On the other hand, the values provided by the experts from Kenya and the Democratic Republic of the Congo seemed to be higher than those reported in population-based survey studies where PCR was used as gold standard (e.g., [ 28 , 29 ]). Nonetheless, the one-way sensitivity analyses showed that the true prevalence estimates in all three countries were robust against misspecification of this prior.…”
Section: Discussionmentioning
confidence: 60%
“…The gametocytes were then tested regarding their sexual differentiation capability in vitro, using 100 µL gametocyte culture (stage V) at 27 °C for 20 min [31]. Samples were then spun at 2500 rpm for 3 min, pellets were analysed by Giemsa staining and gametes were visualized at 40× using a Primo Star Carl Zeiss microscope [32].…”
Section: Plasmodium Falciparum In Vitro Culturementioning
confidence: 99%